Analysis of Item Response Theory in Science Literacy Assessment Containing Local Wisdom and Pancasila Student Profile - Dewantara, Dewi; Wati, Mustika; Hartini, Sri; Haryandi, Surya; Fajariah, Ismi; Syifa, Nuzuluna Aulia; Fitri, M Riduan (Tarbiyah : Jurnal Ilmiah Kependidikan, 2024)
Science literacy assessment is critical because it helps measure people's understanding of scientific concepts and ensures the effectiveness of science education. This study aimed to identify the quality of the instrument based on item response theory in assessing high school physics science literacy. This instrument is found in particle dynamics material. This type of research is quantitative descriptive. The location of data collection was in three schools in Banjarmasin City. The sample was obtained by cluster random sampling. The validity of the Rasch program was obtained from the results of the fit order items compared to the MNSQ and ZSTD value criteria. The validity test and discriminatory power analysis results showed that three invalid questions had to be discarded. The results showed that the developed science literacy instrument had a level of difficulty in the middle, so the instrument was suitable for both high-ability and low-ability students. This study implies that this assessment can help students relate physics concepts to local culture, increasing the relevance of learning and producing students who are not only academically competent but also have social and cultural awareness.